THE VAGARIES OF VAGUENESS: RETHINKING THE CFAA AS A PROBLEM OF PRIVATE NONDELEGATION. (Harvard Law Review, 2013)
The article discusses the legal concept of vagueness in relation to private nondelegation and the U.S. Computer Fraud and Abuse Act of 1986 (CFAA) which was reportedly established as a means of combating computer hacking. The CFAA's definition of a "protected computer" is mentioned, along with misdemeanors, felonies, and the damages associated with violations of the CFAA. A rule of lenity is examined, as well as criminal liability and a void-for-vagueness legal doctrine.